The deadliest sin - Westerson, Jeri (Westerson, Jeri. Crispin Guest novels., 2022)
"1399, London. A drink at the Boar's Tusk takes an unexpected turn for Crispin Guest, Tracker of London, and his apprentice, Jack Tucker, when a messenger claims the prioress at St. Frideswide wants to hire him to investigate murders at the priory. Two of Prioress Drueta's nuns have been killed in a way that signifies two of the Seven Deadly Sins, and she's at her wits end. Meanwhile, trouble is brewing outside of London when the exiled Henry Bolingbroke, the new Duke of Lancaster, returns to England's shores with an army to take back his inheritance. Crispin is caught between solving the crimes at St. Frideswide's Priory, and making a choice once more whether to stand with King Richard or commit treason again."--Publisher.